Analisis Faktor-Faktor yang Berpengaruh terhadap Ketimpangan Pendapatan di Jawa Timur Tahun 2021 - Ike Sugiarti; Rendra Erdkhadifa (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Income inequality is defined as an uneven distribution of income in an area that is not supposed to be. As a result of the occurrence of income inequality that is too high will have a negative impact on social and economic life, as well as the emergence of a conflict. Therefore, a problem raised in this study is the factors with the assumption that it affects the emergence of inequality, which aims to find out the causes of income inequality which are influenced by what factors. The quantitative approach is a method used in this study and the use of this type of research is associative. A total of 38 regencies/cities in the province of East Java in 2021 will be used as populations and research samples. The sampling technique used is non-probability sampling and uses saturated sampling, as well as processing the research sample using multiple linear regression analysis. Where the results shown are on the quality factor of human resources with indicators including: the human development index, economic growth, the level of open response and the average education has a positive and significant effect on income inequality in districts/cities of East Java province. Meanwhile, the population factor has a positive and insignificant effect on income inequality in the districts/cities of East Java province. Keywords: Average Education; Economic Growth; Human Development Index; Income Inequality; Open Unemployment Rate; Population